Four weeks of hypoxia training improves cutaneous microcirculation in trained rowers - Meng, Z.; Gao, B.; Gao, H.; Ge, P.; Li, T.; Wang, Y. (Institute of Physiology (IPHYS) of the Czech Academy of Sciences (CAS), 2019)
Hypoxia training can improve endurance performance. However, the specific benefits mechanism of hypoxia training is controversial, and there are just a few studies on the peripheral adaptation to hypoxia training. The main objective of this study was to observe the effects of hypoxia training on cutaneous blood flow (CBF), hypoxia-inducible factor (HIF), nitric oxide (NO), and vascular endothelial growth factor (VEGF).Twenty rowers were divided into two groups for four weeks of training, either hypoxia training (Living High, Exercise High and Training Low, HHL) or normoxia training (NOM). We tested cutaneous microcirculation by laser Doppler flowmeter and blood serum parameters by ELISA. HHL group improved the VO2peak and power at blood lactic acid of 4 mmol/l (P4) significantly. The CBF and the concentration of moving blood cells (CMBC) in the forearm of individuals in the HHL group increased significantly at the first week. The HIF level of the individuals in the HHL group increased at the fourth week. The NO of HHL group increased significantly at the fourth week. In colusion, four weeks of HHL training resulted in increased forearm cutaneous blood flow and transcutaneous oxygen pressure. HHL increases rowers` NO and VEGF, which may be the mechanism of increased blood flow. The increased of CBF seems to be related with improving performance.